Results of Comparative Study of Fractures Fixed with DCP and Nailing (Medical Forum Monthly, 2024)
Introduction: The treatment methods of the fractures of humerus are treated in many ways. Interlocking nails and plates have both stood the test of time but the present study looks at both methods scientifically.Study Design: Prospective, comparative studyPlace and Duration of Study: This study was carried out at Ghazi Medical College, D.G.Khan from 07.01.2013 to 25.02.2015.Materials and Methods: A total of 40 patients were included in the study. It was a, study of two groups of patients of fractures of humerus treated with dynamic compression plate versus with interlocking nails.Results: Fractures in both groups healed uneventfully without significant complications.Conclusion: Both modes of treatment can be recommended for the treatment of fractures of the shaft of Humerus with minimal chances of complications.